Perceived job insecurity, facades of conformity, emotional exhaustion and disengagement - Tshepo N. Tumelo; Fiona M. Donald (SA Journal of Industrial Psychology)
Orientation: Job insecurity is a pressing concern for many and is known to have negative outcomes for organisations and individuals. It is important to understand how employees respond to job insecurity and the effectiveness of these strategies.